Forecasting the Spanish economy with an augmented VAR-DSGE model - Gonzalo Fernández-de-Córdoba; José L. Torres (SERIEs - Journal of the Spanish Economic Association, 2011)
Over the past 10 years dynamic stochastic general equilibrium (DSGE) models have become an important tool in quantitative macroeconomics. However, DSGE models were not considered as a forecasting tool until very recently. The objective of this paper is twofold. First, we compare the forecasting ability of a canonical DSGE model for the Spanish economy with other standard econometric techniques. More precisely, we compare out-of-sample forecasts obtained from different estimationmethods of the DSGE model with the forecasts produced by a VAR and a Bayesian VAR. Second, we propose a new method for combining DSGE and VAR models (in what we have called Augmented VARDSGE) through the expansion of the variable space where the VAR operates with artificial series obtained from a DSGE model. The results indicate that the out-of-sample forecasting performance of the proposed method is capable of competing with all the considered alternatives, and thus even a simple canonical RBC model contains useful information that can be used for forecasting purposes.
Keywords: C53; E32; E37; 330; DSGE models; forecasting; VAR; BVAR; Konjunkturprognose; Dynamisches Gleichgewicht; VAR-Modell; Bayes-Statistik; Prognoseverfahren; Spanien